2022
DOI: 10.1038/s41598-022-12857-3
|View full text |Cite|
|
Sign up to set email alerts
|

Finite element analysis for ternary hybrid nanoparticles on thermal enhancement in pseudo-plastic liquid through porous stretching sheet

Abstract: Thermal performance can be enhanced due to the mixing of nanoparticles in base fluid. This research discusses the involvement of ternary hybrid nanoparticles in the mixture of pseudo-plastic fluid model past over a two dimensional porous stretching sheet. Modelling of energy equation is carried out in the presence of external heat source or sink and viscous dissipation. The flow presenting equations and derived in Cartesian coordinate system under usual boundary layer theory in the form of complex coupled part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Wang et al 44 presented a strategy for tri-HNFs combination in ethylene glycol encompassing movable diffusion and current conductivity using non-Fourier’s scheme. Sohail et al 45 , 46 suggested a study of tri-HNFs diffusion species and energy transfer in material prejudiced by instigation energy and heat source. Nazir et al 47 presented a significant manufacture of current dynamism in incompletely ionized hyperbolic tangent substantial created by ternary tri-HNFs 48 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 44 presented a strategy for tri-HNFs combination in ethylene glycol encompassing movable diffusion and current conductivity using non-Fourier’s scheme. Sohail et al 45 , 46 suggested a study of tri-HNFs diffusion species and energy transfer in material prejudiced by instigation energy and heat source. Nazir et al 47 presented a significant manufacture of current dynamism in incompletely ionized hyperbolic tangent substantial created by ternary tri-HNFs 48 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [26] used C-shaped grooves at the tip clearance to study the influence of C-shaped grooves of different sizes on TLV, which effectively improved the lift coefficient of NACA0009. Nazir et al [27][28][29][30][31] take ethylene glycol with nanoparticles behaves as the research object and consider the importance of temperature gradient in studying fluid behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier's A study of THNFs distributionclasses and energy transmission in materials affected by input energy and heat source was recommended by Sohail et al 59 , 60 . A large manufacturing of current energy in partially ionized hyperbolic tangent material formulated by ternary THNFs was disclosed by Nazir et al 61 .…”
Section: Introductionmentioning
confidence: 99%